INVESTIGATION OF MECHANICAL PROPERTIES OF ASPHALT CONCRETE CONTAINING STYRENE BUTADIENE STYRENE - Kok, Baha Vural; Kuloglu, Necati (Yildiz Technical Univ, 2008)
This paper discusses the laboratory design of continuously graded asphaltic concrete mixtures containing styrene butadiene styrene (SBS). The purpose of this study is to evaluate mechanical properties of control and SBS modified asphalt mixtures. Furthermore rheological properties of conventional and modified asphalt in different SBS content were studied. AC-10 was used as binder in the study. Two different aggregate, limestone and basalt, were used in the experiments to evaluate the effect of aggregate-binder interaction. Marshall stability, indirect tensile strength, indirect tensile stiffness modulus and static creep stiffness tests were performed on mixtures. The specimens prepared with limestone showed greater mechanical properties than that of the specimens prepared with basalt. It was determined that for the resilient modulus a linear relation and for the creep stiffness a polynomial relation is exists with SBS content. The higher SBS content provides the higher properties however the increasing rate of improvement properties by adding SBS is decreased after 5 percent. So the effective and economical value of SBS content is considered as 5 percent by weight of binder.
Keywords: Asphalt concrete; SBS; mechanical properties